Planning Culture as a System of Meaning. A Study Using the Example of Cooperative Green Urban Development in Düsseldorf, Germany - Sondermann, Martin (Raumforschung und Raumordnung | Spatial Research and Planning, 2017)
How is the normative ideal of cooperative urban planning working in practice? Taking the case of green urban development in Düsseldorf (Germany) the analysis is focused on the cooperation between civil society and political-administrative actors. Thereby planning practice is qualitatively analysed from a cultural perspective. The empirical observations are theorised based on a Grounded Theory approach leading to a model of planning culture. It is shown how a ‘culture of cooperation’ has emerged in Düsseldorf’s green urban development, including a living tradition of cooperation and shared orientations of the actors. This culture is observable in the institutional scopes of actions and the adaptation of organisational structures and procedures. The theoretical output of this research illustrates an understanding of planning which emphasises the specific forms of negotiating spatial development on the local level. Ultimately local planning cultures are described as context-specific systems of meaning, which have emerged over time through processes of communication, learning and rapprochement between the actors involved. These systems of meaning guide planning-related actions and manifest in the ways spaces are socially produced.
Keywords: Planning theory; Planning practice; Planning culture; Cooperation; Civil society; Urban green spaces